DOES COMMUNICATION NETWORK HETEROGENEITY MODERATED BY ACADEMIC LEVEL PREDICT STUDENT SUBJECTIVE WELL-BEING? - Rahardjo, Wahyu; Indryawati, Rini; Fuad, Afmi; Qomariyah, Nurul; Andriani, Inge; Harsanti, Intaglia; Salve, Henny Regina (Arjwa: Jurnal Psikologi, 2024)
After the pandemic, students are still facing issues related to subjective well-being. Student behavior in communicating online with social media with various people with diverse backgrounds and also demographic factors such as academic level are factors that are thought to be able to predict student subjective well-being. The purpose of this study is to empirically ascertain whether communication network heterogeneity moderated by academic level has an effect on student subjective well-being. The participants of this study were 437 students in the Jakarta Greater area. Theoretical models are made to fit with empirical models. The results showed that academic level did not have a significant role in moderating the effect of communication network heterogeneity on student subjective well-being. That is, communication network heterogeneity itself is quite strong in predicting student subjective well-being. Other results are discussed later.